Immuntherapien bei Gliomen = Glioma immunotherapy - Sahm, Katharina; Bunse, Lukas; Mildenberger, Iris; Wick, Wolfgang; Platten, Michael (Der Onkologe, 2017)
BackgroundImmunotherapeutic approaches for treatment of malignant gliomas aim at inducing effective anti-tumor immune responses while counteracting the immunosuppressive tumor microenvironment. Despite extensive preclinical and clinical research during the last decades, there are currently no approved immunotherapeutic drugs for primary brain tumors; however, neuro-oncoimmunology is currently experiencing major interest due to new diagnostic and targeted therapy options as well as due to promising results in systemic tumors.ObjectiveThis article provides an overview of current concepts for glioma immunotherapy and summarizes the results of available clinical trials.ResultsWhile first clinical experiences with the administration of immune checkpoint inhibitors for gliomas did not raise any safety concerns, the efficacy of immune checkpoint monotherapy for malignant gliomas appears to be limited in an unselected patient population. Clinical results on combination treatment, such as T cell-based therapy approaches with antigen-specific vaccinations are pending. This involves mostly peptide vaccines that are directed against tumor antigens in order to generate an effective and at the same time specific anti-tumor immune response. In addition to vaccines against individually variable antigens, recurrent neoepitopes are particularly suitable as a target of vaccination, such as a splice variant of the epidermal growth factor (EGFRvIII) occurring in glioblastomas and a point mutation occurring in diffuse gliomas in the gene of isocitrate dehydrogenase-1 (IDH1R132H).